Thermophilic fermentation enhanced by eggshell-derived hydroxyapatite for sustainable hydrogen production - Zisha, Shishita Zahan; Man, Hasfalina Che; Omar, Rozita; Rashid, Suraya Abdul; Ping, Tan Jian; Fairuz, Shareena; Manaf, Abdul; Mumtaz, Tabassum; Jamali, Nur Syakina (Springer, 2025)
This study presents the eco-friendly synthesis of Hydroxyapatite (HAP) using chicken eggshell biowaste as a sustainable calcium source to enhance biohydrogen production. The stoichiometric ratio of Ca/P was determined to be 1.67 by evaluating pH, temperature, and calcination time, revealing that pH 10.5, temperature 950ᵒC, and calcination time of 2 h were optimal. Structural and morphological characterization confirmed the successful formation of crystalline HAP with 78% crystallinity (XRD), accurate Ca/P ratio (EDS), and phosphate group presence (FTIR). The synthesized HAP was applied as a bio-additive in thermophilic dark fermentation using a Thermoanaerobacterium-enriched sludge. The optimal HAP dosage (560 mg/L) yielded the highest hydrogen yield of 1.085 mol H2/mol sugar and a hydrogen production rate of 27.969 mL H2/(L h), representing a 59.73% increase over the control. Volatile fatty acid analysis and microbial profiling confirmed enhanced butyrate metabolism and a dominant presence of Thermoanaerobacterium thermosaccharolyticum. This work demonstrates a novel waste-to-value approach by integrating green-synthesized HAP with thermophilic fermentation, contributing to both waste valorization and renewable hydrogen production.